(untitled) (Journal of the College of Basic Education, 2025)
The effect of tactical exercises by playing from the parties on the development of complex skill performance among young football players Wing play in football primarily relies on the use of wide areas to penetrate the opponent’s defense and deliver crosses into the penalty area. The striker, in this context, is a player who moves fluidly between attacking and defensive lines without occupying a fixed position on the field. This player’s continuous movement and positional shifts can create confusion in the opponent’s defense by drawing defenders away from their designated zones.The research problem emerged from the researcher’s experience as a coach for youth football teams, where he observed a noticeable weakness in the speed of skill execution among youth players when faced with varied and complex game situations requiring quick and accurate decision-making.To address this issue, the researcher adopted the experimental method and selected the research sample randomly using the method of two equivalent groups. A set of tests was chosen to measure compound skill performance, followed by pre-testing. The intervention included implementing a series of tactical exercises over a period of seven weeks.The results indicated that employing tactical drills involving the use of a false striker in combination with wing-based attacks significantly improved compound skill performance among youth football players. The researcher recommends the adoption of such exercises in youth football training programs to enhance players’ tactical awareness and skill execution under game-like conditions.